Jumlah Sel Osteoklas pada Tulang Alveolar Daerah Tekanan Gigi Tikus yang Diinduksi Gaya Mekanis Ortodonti - Samahi Arrahma; Herniyati Herniyati; Dwi Prijatmoko (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
The mechanical force of orthodontics produces areas of pressure and pull. In the pressure area occurs resorption of alveolar bones carried out by osteoclast cells. The study aims to find out the change in the number of osteoclast cells in the alveolar bone pressure area of mouse teeth that induced mechanical force orthodontics. 36 male rats are divided into 6 groups. Group K: mice are not given a mechanical style of orthodontics. Group P: mechanically styled orthodontics (GMOs). GMOs in mice were administered to the upper jaw molar-1 (M-1) teeth (RA) right and in both RA incisive teeth using Ni-Ti Orthodontic Closed Coil Spring diameter 0.01 inches in orthodontic force of 3.5 oz = 85.05 gr/cm2 = 10 grF for 1 week, 2 weeks and 3 weeks. The results of the study were 1 week (1.99), 2 weeks (1.92), and 3 weeks (1.75). Conclusion of mechanical administration of orthodontic force increases the number of osteoclast cells on the 8th day (1 week), the 15th (2 weeks), and the 22nd (3 weeks). Based on the observation time there was a decrease in the number of osteoclast cells from 1 week to 2 weeks then to 3 weeks but not significant.